Mikroekonomické modely trhu s externalitami, zobecněný Coaseho teorém - Jiří Hlaváček; Michal Hlaváček (Charles University in Prague, Institute of Economic Studies (IES), 2008)
– Three original microeconomic models of an externality market are described: (1) model of the marketable permits for exhalations emission, (2) model of optimal financial satisfaction of a damage caused by a negative externality in the economy with agents maximizing probability of their survival (generalized Coase theorem) and (3) model of optimal financial favor for agents provided a positive externality.
Keywords: D62; D01; 330; negative externalities; marketable permits for exhalations; generalized Coase theorem; maximizing of the probability of an economic survival; positive externalities; Externer Effekt; Coase-Theorem; Theorie